Lichen Sclerosus or Vulvar Angiokeratoma: A Diagnosis That Is Not Always So Easy - Vincenzo De Giorgi; Gabriella Perillo; Pietro Antonini; Giovanni Cecchi; Biancamaria Zuccaro; Elisabetta Magnaterra; Eleonora Castellacci; Daniela Massi (Dermatology Practical & Conceptual)
--